Constructing an Urban Population Model for Medical Insurance Scheme Using Microsimulation Techniques. (1st March 2012) - Xiong, Linping; Zhang, Lulu; Tang, Weidong; Ma, Yuqin
Abstract : China launched a pilot project of medical insurance reform in 79 cities in 2007 to cover urban nonworking residents. An urban population model was created in this paper for China's medical insurance scheme using microsimulation model techniques. The model made it clear for the policy makers the population distributions of different groups of people, the potential urban residents entering the medical insurance scheme. The income trends of units of individuals and families were also obtained. These factors are essential in making the challenging policy decisions when considering to balance the long-term financial sustainability of the medical insurance scheme.